Bad reputation [videorecording (DVD)] - Armstrong, Billie Joe, 1972-; Bingenheimer, Rodney; Brinkman, Carianne; Jett, Joan (Magnolia Home Entertainment, 2018)
It's true, Joan Jett became mega-famous from the number-one hit "I Love Rock n Roll," but that's only part of the story. This documentary gives a wild ride as Jett and her close friends tell you how it really was in the burgeoning's 70s punk scene and the rocky road to rock stardom decades on. Their interviews are laced with amazing archival footage.